Effect of action learning on digital storytelling education for fashion students. Issue 3 (2nd September 2022) - Kim, Sejin
ABSTRACT: Digital moving images and storytelling method are increasingly used for fashion presentation in the digital media environment. However, there has been a lack of the education for fashion students. This study aims at considering action learning as an effective learning method for fashion students who specially are unfamiliar with digital film making. A three-unit teaching plan based on an action learning curriculum for digital fashion film production education was designed and its teaching method applied to practicum classes. The result reflected that the education had a potential to improve the expression ability of fashion design. The application of the action learning method for non-practical fashion students is shown to achieve the following: (1) A high learning effect for a limited time in acquiring the new programme required in the practicum class. (2) Efficiency in developing rich research and ideas from various perspectives, (3) Strengthening responsibility. (4) Improving problem-solving ability.